Risk assessment of fatal accidents due to work at heights activities using fault tree analysis: case study in Malaysia - Zermane, Abderrahim; Mohd Tohir, Mohd Zahirasri; Baharudin, Mohd Rafee; Mohamed Yusoff, Hamdan (Elsevier, 2022)
Fatal falls from heights accidents represent a threat to any industry's development and progress. It is crucial to understand how these accidents evolve from a simple ‘near miss‘ into a ‘fatal accident‘. In recent years, Malaysia's construction industry suffered an increasingly alarming number of fatal falls from heights accidents. Fatal accident numbers that were reported and investigated had a noticeable increase from 2013 to 2017. The purpose of this study is to assess the risks associated with falls from heights fatal accidents, which ultimately will be able to help provide the data for proactive prevention against this type of accident. This study used two different risk assessment methods. The first risk assessment consists of a statistical analysis of the collected data. The second risk assessment includes a fault tree analysis. Data extracted from the Department of Occupational Safety and Health Malaysia were used as input for the risk assessment. Results indicate several significant causes that need to be handled immediately. Some of these causes are failure to wear Personal Protective Equipment with an 85.93% occurrence rate, the lack of supervision and leadership with 89.84%, and the absence of work standards or the inability to follow them correctly with 85.15%. This study will help identify root causes, immediate causes, accidents scenarios, and finally the probability and urgency when investigating fatal falls from heights.